Answer: B.) PQRST
Step-by-step explanation:
There are no options but if its the same question I just had on a test then this is the answer..
Hope this helps..
By definition, we have
![|p+2| = \begin{cases} p+2 &\text{ if } p+2 \geq 0 \\-p-2 &\text{ if } p+2 < 0 \end{cases}](https://tex.z-dn.net/?f=%20%7Cp%2B2%7C%20%3D%20%5Cbegin%7Bcases%7D%20p%2B2%20%26%5Ctext%7B%20if%20%7D%20p%2B2%20%5Cgeq%200%20%5C%5C-p-2%20%26%5Ctext%7B%20if%20%7D%20p%2B2%20%3C%200%20%5Cend%7Bcases%7D%20)
So, we have to solve two different equations, depending of the possible range for the variable. We have to remember about these ranges when we decide to accept or discard the solutions:
Suppose that ![p+2\geq 0 \iff p \geq -2](https://tex.z-dn.net/?f=%20p%2B2%5Cgeq%200%20%5Ciff%20p%20%5Cgeq%20-2%20)
In this case, the absolute value doesn't do anything: the equation is
![p+2 = 10 \iff p = 10-2 = 8](https://tex.z-dn.net/?f=%20p%2B2%20%3D%2010%20%5Ciff%20p%20%3D%2010-2%20%3D%208%20)
We are supposing
, so we can accept this solution.
Now, suppose that
. Now the sign of the expression is flipped by the absolute value, and the equation becomes
![-p-2 = 10 \iff -p = 12 \iff p = -12](https://tex.z-dn.net/?f=%20-p-2%20%3D%2010%20%5Ciff%20-p%20%3D%2012%20%5Ciff%20p%20%3D%20-12%20)
Again, the solution is coherent with the assumption, so we can accept this value as well.
H + 732 = -194
* combine like terms
H = -194 - 732
H = -926
So you just subsitute -3 for x
f(-3)=-(-3)+15
f(-3)=3+15
f(-3)=18
answer is C
18
For the answer to the question, i<span>f a function uses variables other than x and y for its input and output variables, you take the original equation and solve for the input variable to find the inverse.
The answer is Simply true. But in real life it's false.
I hope my answer helped you.</span>